PENGARUH PENGENCER SEMEN TERHADAP ABNORMALITAS DAN DAYA TAHAN HIDUP SPERMATOZOA KAMBING LOKAL PADA PENYIMPANAN SUHU 5ºC - Ridwan Ridwan (Universitas Tadulako, 2009)
The research objective was to determine the effects of semen diluter on the abnormality and survival of local goat spermatozoa maintained at 50C. The research used a Completely Randomized Design (CRD) of three different diluter (NaCl 0.9%, Lactate Ringer, and Dextrose Ringer) with six replicates. Analysis of variance showed that the treatment effects were highly significant (P<0.01) on both the abnormality and survival of the goat spermatozoa. The spermatozoa abnormality was significantly higher in the lactate ringer treatment (6.26%) than any other treatment. Similarly, the survival of the goat spermatozoa in the dextrose ringer and NaCl treatment were significantly larger (77 and 80.5%) than that in the lactate ringer treatment (66,3%).